Deletion of Smooth Muscle Lethal Giant Larvae 1 Promotes Neointimal Hyperplasia in Mice - Zhang, Ya; Yuan, Peidong; Ma, Xiaoping; Deng, Qiming; Gao, Jiangang; Yang, Jianmin; Zhang, Tianran; Zhang, Cheng; Zhang, Wencheng (Frontiers in Pharmacology, 2022)
Vascular smooth muscle cell (VSMC) proliferation and migration contribute to neointimal hyperplasia after injury, which causes vascular remodeling related to arteriosclerosis, hypertension and restenosis. Lethal giant larvae 1 (LGL1) is a highly conserved protein and plays an important role in cell polarity and tumor suppression. However, whether LGL1 affects neointimal hyperplasia is still unknown. In this study, we used smooth muscle-specific LGL1 knockout (LGL1SMKO) mice generated by cross-breeding LGL1flox/flox mice with α-SMA-Cre mice. LGL1 expression was significantly decreased during both carotid artery ligation in vivo and PDGF-BB stimulation in vitro. LGL1 overexpression inhibited the proliferation and migration of VSMCs. Mechanistically, LGL1 could bind with signal transducer and activator of transcription 3 (STAT3) and promote its degradation via the proteasomal pathway. In the carotid artery ligation animal model, smooth muscle-specific deletion of LGL1 accelerated neointimal hyperplasia, which was attenuated by the STAT3 inhibitor SH-4-54. In conclusion, LGL1 may inhibit neointimal hyperplasia by repressing VSMC proliferation and migration via promoting STAT3 proteasomal degradation.